Evaluation of inter‐individual differences in gut bacterial isoflavone bioactivation in humans by PCR‐based targeting of genes involved in equol formation - Braune, A.; Blaut, M. (Journal of applied microbiology, 2018)
Aim To identify human subjects harbouring intestinal bacteria that bioactivate daidzein to equol using a targeted PCR‐based approach. Methods and Results In a pilot study including 17 human subjects, equol formation was determined in faecal slurries. In parallel, faecal DNA was amplified by PCR using degenerate primers that target highly conserved regions of dihydrodaidzein reductase and tetrahydrodaidzein reductase genes. PCR products of the expected size were observed for six of the eight subjects identified as equol producers. Analysis of clone libraries revealed the amplification of sequences exclusively related to Adlercreutzia equolifaciens in four of the subjects tested positive for equol formation, whereas in three of the equol producers, only sequences related to Slackia isoflavoniconvertens were observed. No amplicons were obtained for one equol‐forming subject, thus suggesting the presence of nontargeted alternative genes. Amplicons were only sporadically observed in the nonequol producers. Conclusion The majority of human subjects who produced equol were also detected with the developed PCR‐based approach. Significance and Impact of the Study The obtained results shed light on the distribution and the diversity of known equol‐forming bacterial species in the study group and indicate the presence of as yet unknown equol‐forming bacteria.